Effective Communication Skill: Doctor – Patient Consultation - Saptawati Bardosono; Pittara Pansawira; Mia Puspita Ratih (World Nutrition Journal, 2018)
Everyone, including physicians/doctors knows how to communicate. Communication skill involves how we apply a systematic cycle of sending message, receiving and interpreting it before we give a feedback. However, people only perceived communication as practicing sending the message. And, when receiving a message the feedback-step is the most often neglected. Actually, the feedback-step is the most critical part in which it closes the communication cycle and confirms the understanding of the message.Furthermore, there is a deeper development of communication in which we need to stress into three approaches, i.e. being present, active listening and active empathy. By being present then we can clear the clutter of mental distraction and focus on the immediate communication task at hand. Active listening is needed to apply specific listening-for-understanding techniques that confirm awareness, while active empathy is important to process information for a true awareness of other’s needs. All this approaches take times, of course, however we can anticipate it by practicing effective communication.